Prinsip–Prinsip Good Governance Dalam Pelayanan Publik: good governance, pelayanan publik, negara - Aisyam (JAMAK: Jurnal Administrasi Manajemen dan Kepemimpinan, 2020)
The principles of good governance applied by various countries are a good start to restore the positive image of the public service community which seems strange, convoluted, and slow. Good governance is an important part of state governance to meet the needs of the community through practices based on law, social justice and the conditions for transparency practices. This article is the result of the study the theoretical concept about the good governance principles in the public service bureaucracy in Indonesia. Study results showed that the application of the principles of good governance so far hasn’t been going well. The misappropriation of bureaucrats to fulfill personal interests is still an obstacle. However, the government still strives to provide effective, efficient and fast public services as well as problem solving which become obstacles in providing public services in accordance with the principles and characteristics of good governance expected by the public.